2014
DOI: 10.1016/j.freeradbiomed.2014.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Activation of c-Src: A hub for exogenous pro-oxidant-mediated activation of Toll-like receptor 4 signaling

Abstract: Summary To study the role of c-Src kinase in prooxidant-induced stimulation of TLR4, we used LPS-EK and MPLA as TLR4 specific agonists and positive controls, and SIN-1 and PPC as prooxidant sources. We used HEK-Blue mTLR4 cell line that is stably transfected with mouse TLR4 and that expresses optimized SEAP reporter under the control of a promoter inducible by NF-κB transcription factor. The level of SEAP released due to TLR4 stimulation was a measure of NF-κB activation. Treatment with either the prooxidants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 79 publications
2
9
0
Order By: Relevance
“…Mechanistically, this is of significance because it confirms that HMGB1 can be released from cells either actively in a regulated process, or passively during necrosis [41, 42]. Our previous work showed that over 94 % of cells remained viable after treatment with PPC (5 μM) and SIN-1 (1.0 mM) as used in the present experiments [32]. These results suggest that prooxidant-induced HMGB1 release from HEK-Blue mTLR4 cells is not caused by cell death, but is likely due to an active process regulated by the levels of iROS.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Mechanistically, this is of significance because it confirms that HMGB1 can be released from cells either actively in a regulated process, or passively during necrosis [41, 42]. Our previous work showed that over 94 % of cells remained viable after treatment with PPC (5 μM) and SIN-1 (1.0 mM) as used in the present experiments [32]. These results suggest that prooxidant-induced HMGB1 release from HEK-Blue mTLR4 cells is not caused by cell death, but is likely due to an active process regulated by the levels of iROS.…”
Section: Discussionsupporting
confidence: 69%
“…We had previously shown in vivo and in vitro that PPC could activate NF-κB mainly through a TLR4-dependent pathway, which was attenuated by prior treatment with antioxidants [23,32]. Our initial experimental evidence for the involvement of prooxidants in promoting HMGB1-induced NF-κB activation is based on SEAP and TNF-α release, and inhibition of their release with TLR4 neutralizing pAb and HMGB1 (BoxA) fragment, a specific antagonist of HMGB1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genistein, a broad-spectrum inhibitor of tyrosine kinases, has been shown to display strong antiinflammatory activity (Kim et al, 2005). Moreover, suppression of Syk or Src by knockdown or conditional knockout strategies resulted in macrophages that failed to express various proinflammatory cytokines Karki et al, 2014;Miller et al, 2012). Although the exact mechanism by which Src and Syk activate NF-κB is not fully understood, these data strongly indicate that Src and Syk could play critical roles in TLR-mediated inflammatory responses and could also be the pharmacological targets of Pa-ME.…”
Section: No Production (% Of Controlmentioning
confidence: 99%